Fluid-phase-equilibrium prediction of fluorocompound-containing binary systems with the predictive E-PPR78 model. (January 2017) - Qian, Jun-Wei; Privat, Romain; Jaubert, Jean-Noël; Coquelet, Christophe; Ramjugernath, Deresh
Highlights: The applicability range of the predictive E -PPR78 equation of state is extended. Six new groups: C2 F6, CF3, CF2, =   CF 2   ⇔   =   CF, C2 H4 F2 and C2 H2 F4 are added. The E -PPR78 model is now applicable to fluorocompound-containing mixtures. Abstract: In order to reduce the overall emissions of greenhouse gases and to be in compliance with the current environmental regulations, a new class of refrigerants has appeared. Such refrigerants are generally multi-component systems that contain a fluorocompound mixed with CO2 and/or an alkane. In order to design processes involving such blends or to implement a product-design approach aimed at identifying new refrigerant mixtures, an equation of state (EoS) able to predict the properties of fluorocompound-containing systems is required. In order to reach this goal, it was decided in this study to add six fluorinated groups to the E nhanced-PPR78 model which combines the Peng–Robinson EoS and a group contribution method aimed at estimating the binary interaction parameters, kij ( T ), involved in Van der Waals one-fluid mixing rules.